2017
DOI: 10.1177/0009922817696464
|View full text |Cite
|
Sign up to set email alerts
|

Patient Feedback Requirements for Medical Students: Do Perceived Risks Outweigh the Benefits?

Abstract: Patient feedback has increasingly become part of medical students' training and formative assessment. We conducted a qualitative study using focus groups to explore students' experiences soliciting patient feedback, including the benefits, challenges, and potential strategies to obtain it. Fifteen medical students participated. Thematic analysis revealed students' (1) discomfort soliciting feedback and concern of being viewed as self-serving; (2) concerns about eroding patient trust; (3) indifference to nonspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The authors of previous studies and patient surveys have often advocated for anonymous patient feedback as a favourable approach to creating a safe environment in which to provide feedback regarding patients’ subjective experiences of an encounter [ 12 , 30 ]. In the current study, patients were not anonymous, which could have affected their willingness both to participate in the study and provide feedback due to their plausible dependability upon their caregiver [ 19 , 47 ]. The patients in this study indicated that the items’ content gave them opportunities to respond to specific aspects of an encounter and to assess concrete, non-emotional aspects of their experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of previous studies and patient surveys have often advocated for anonymous patient feedback as a favourable approach to creating a safe environment in which to provide feedback regarding patients’ subjective experiences of an encounter [ 12 , 30 ]. In the current study, patients were not anonymous, which could have affected their willingness both to participate in the study and provide feedback due to their plausible dependability upon their caregiver [ 19 , 47 ]. The patients in this study indicated that the items’ content gave them opportunities to respond to specific aspects of an encounter and to assess concrete, non-emotional aspects of their experience.…”
Section: Discussionmentioning
confidence: 99%
“…Students’ clinical supervisors are often the main providers of feedback regarding communication and patient-centeredness [ 18 ]. Patients’ participation in medical education can facilitate students’ abilities to evaluate their own communication and patient-centeredness proficiencies, positively influencing patients’ experiences of healthcare [ 19 , 20 ]. Traditionally, patients’ involvement in medical education has been passive and objectified, hence illustrating specific conditions or clinical findings [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study pinpoints the elements of the consultation where they are providing a unique and valuable perspective. This responds to Chua and Bogetz's [18] call for patients to be empowered to see themselves as teachers who have an impact on student learning through feedback.…”
Section: Implications For Social Learning In Patient-centred Curriculummentioning
confidence: 99%
“…References to multisource feedback in medical student learning tend to focus on peer and self-assessment, not patient assessment. However recently, Chua and Bogetz [18] shifted their focus from the post-graduate realm to explore medical students' solicitation of patient feedback in the acute setting and this work provides useful insights which can guide processes for students seeking meaningful patient feedback. Despite this, understanding what perspective-specific role patients play as a feedback source in medical school learning environments has yet to be fully investigated in terms of specifically what students can expect from patients that may be different to what they receive from their clinical tutors, to enable them to synthesise and utilise such feedback in their development.…”
Section: Introductionmentioning
confidence: 99%